Persepsi Mahasiswa Terhadap Pembelajaran dengan Menggunakan Metode Latihan Terbimbing pada Mata Kuliah Pengembangan Program Pembelajaran Biologi di UMMY Solok - Eka Wati, Darmanella Dian (Jurnal Bioconcetta, 2018)
Lessons are well planned by the teacher will provide good results as well. The ability to plan learning began in studied by prospective teachers in the university level biology courses Learning Program Development Biology. This course is intended to provide supplies for students as prospective teachers so that later on the activities of Field Education or at the time of becoming a teacher of their own competence in making the learning plan. Based on the monitoring results of Field Education students still can not make a good learning plan with them also complained of a given task so that they need guidance in the completion of the task. Therefore perform the process of learning by doing method of guided exercises. And I want to know how students' perceptions of learning by using Method Exercise Course Guided in Education Program Development Biology Subject at UMMY Solok. This research is a descriptive study with a sample of students of Biology is the fifth semester of the school year 2015/2016 totaling 19 people in Biology Education Program UMMY Solok which has made the learning process by using the Guided Training Methods In Learning Course Development Biology Program at UMMY Solok. The sampling technique using total sampling. To obtain the data necessary data collection techniques used in the form of a questionnaire. The type of questionnaire used type of questionnaire enclosed with the form of rating scale. Data analysis technique used is descriptive statistical analysis. Based on research data shows that students UMMY Solok has a good perception once in learning by using Guided Training Methods In Learning Course Development Biology Program at UMMY Solok.